Analysis of the Minimum of Marriageable Age in the Perspective of Theology - Febriani, Evi; Kumaidi, Muhamad; Mu'in, Fathul; Budiman, Arif (Universitas Islam Negeri Raden Fatah Palembang, 2022)
Early marriage is a reality occurred in society. Some parents still have an understanding that getting their children married as soon as possible is part of the solution to lighten the burden on the family. This research aims to reveal what the ideal age for marriage in the theological perspective. This research uses a qualitative approach. Data collection by means of literature study, while data analysis is descriptive qualitative. This research concludes that theologically the age of marriage does not mention numbers, but the principle of maturity of the groom and bride. Therefore, the validity of marriage is not only due to the fulfillment of the pillars, but also develops in the fulfillment of the conditions of marriage. We recommend that the minimum age for marriage still refers to the latest law, in the age of 19 for men and women. This is because if the minimum age is lower than 19, it is still classified as children's age and is no longer relevant to today's era. Age shows a person's maturity to be able to marry in the perspective of theology, health (reproduction), psychology, and the ability to fulfill rights and obligations as husband and or wife.